Knowledge and Practice of Solid Waste and Excreta Management at Secondary Schools in Nawalparasi District. - Maskey, Kashi Palikhe; Lama, Laxmi; Basnet, Ambu; Dhakal, Shiva Prakash (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Solid waste and excreta are unwanted materials in environment. It includes garbage (food waste), rubbish (Paper, plastics, and wood, metal, throw-away containers. glass), demolition product (brackets, masonry, and piper) sewage treatment residue (sludge and solids from the coarse screening of the domestic sewage), dead animal manure and other discarded material. Methods: This cross sectional descriptive study was carried out to find out a study on the practice of solid waste and excreta management among the students of 9-10 grades of Public Secondary schools of Nawalparasi district. For this purpose 168 respondents were provided with semi-structured questionnaire. Results: A total of 96 percent of the respondent said the class room must be clean but in practice it was found that only 85.71 percent students clean the class room. Majority of the respondent said that they dispose the waste in garbage pit but in practice it was not found so the papers were found to thrown haphazardly. Majority of schools had the facility of the dumping site but they were found to adopt bad practice of solid waste management the dumping site was not well managed. The students were found to have knowledge on solid waste and excreta management but they were only the sources of the solid waste in the school. Conclusions: There is a need to raise the awareness about the management of the solid waste among students, teaching and non-teaching staffs of the school. Many teachers and students were the sources of the solid waste. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.12995